Analysing the potential of a simulation-based method for the assessment of CO2 savings from eco-innovative technologies in light-duty vehicles. (15th April 2022) - Gil-Sayas, Susana; Komnos, Dimitrios; Lodi, Chiara; Currò, Davide; Serra, Simone; Broatch, Alberto; Fontaras, Georgios
Abstract: Mandatory targets are set in Europe for Carbon Dioxide (CO2 ) emissions of light-duty vehicles. EU law recognises the potential of certain innovative technologies to contribute to reducing CO2 emissions. Vehicle systems and innovations are becoming increasingly complex, and the accurate quantification of their benefits increasingly difficult. The study investigates the potential of the CO2 MPAS simulator to serve this purpose. Two innovative technologies were studied, Light-emitting diode (LED) lighting systems, efficient alternators (EA), and their combination. The model was validated on detailed test results from eight vehicles. A total of 452 passenger cars, for which test data were available, were subsequently simulated using CO2 MPAS simulator. The mean simulated CO2 savings was 0.91gCO2 /km (LED lights), 0.98 gCO2 /km (EA), and 1.78 gCO2 /km (combined). Results show that simulated CO2 savings were comparable to those calculated using the existing standardised method. For gasoline and diesel vehicles respectively, the difference in CO2 savings between simulated and existing method was 2.8% and 0.14% in the LED lights case, and 0.6% and 0.67% in the alternator case. In the combined case, the difference was calculated to be 1.7% and 0.34%. Similar approaches could be used in the future for accurately capturing the benefits of more complex technologies. Highlights: Assessed the application of software simulation for eco-innovative technologies. CO2 savings from two technologies were simulated with high accuracy. Simulation could support the evaluation of CO2 savings from such technologies. Efficient lighting system or alternator save about 1 gCO2 /km per vehicle. Efficient lighting system and alternator combined save up to 1.8 gCO2 /km per vehicle.